Population dynamic of mackerel scad (Decapterus macarellus Cuvier, 1833) in the Timor Sea - Herwaty, Susy; Mallawa, Achmar; Najamuddin, Najamuddin; Zainuddin, Mukti (Universitas Diponegoro, 2024)
Mackerel scad (Decapterus macarellus) is a fish resource that contributes to the economic sector for fishermen in the province of East Nusa Tenggara province. Its production has increased every year. This study aims to analyze the parameters of the population dynamics of the mackerel scad. Fish samples were collected at the Oeba Fish Landing Base Kupang from April to June 2020. The data analysis used included size structure analyzed descriptively, age group using the Bhattacharya method, growth parameter values (L∞ and K) based on the von Bertalanffy equation, natural mortality using the Pauly method, and Y/R using the Beverton and Holt method. The results showed that the smallest size of the mackerel scad was 7.8 cm (FL), the largest size was 27.8 cm (FL), the average length was 19.63 cm (FL) ± 4.46, the asymptotic length (L∞) = 38.10 cm (FL), the growth parameter value (K)= 0.51 year-1, t0= -0.2996 year-1, The population consists of two to three age groups. the total mortality value (Z)= 2.29 year-1, natural mortality (M) = 1.08 year-1, fishing mortality (F)= 1.22 year-1 and exploitation rate (E)= 0.53 year-1. The actual Y/R value was 0.057 and the relative Y/R was 0.060 grams recruit-1